Erosion Prediction using Universal Soil Loss Equation (USLE) in Posigadan District, South Bolaang Mongondow Regency - R. Radjak, Vhito; Rahim, Yunnita; Rahman, Rival (CELEBES Agricultural, 2024)
Soil erosion refers to removing topsoil caused by the action of water or wind, with its intensity influenced by natural factors specific to the location. This study aims to predict soil erosion, determine tolerable erosion levels, and provide recommendations for land use based on erosion predictions in the Posigadan District, South Bolaang Mongondow Regency, North Sulawesi Province. Conducted between February and April 2024, the research employed the Universal Soil Loss Equation (USLE) method integrated with Geographic Information System (GIS) technology. The USLE method's accuracy depends on factors such as rainfall erosivity (R), soil erodibility (K), slope length and steepness (LS), vegetation cover (C), and conservation practices (P). Meanwhile, GIS proved effective in assessing erosion risks across large areas. The findings revealed that predicted erosion values ranged from 35.59 to 605.06 tonnes/ha/year, categorized from low to very high. Tolerable erosion values ranged from 2.88 to 11.00 tonnes/ha/year. Without conservation measures, areas with low actual erosion were recommended for cultivating crop such as corn and peanuts. In contrast, areas with very high erosion were better suited for plantation commodity like cloves, candlenuts, and cocoa. The study concluded that erosion predictions fell into low, medium, high, and very high categories. Based on these results, land use recommendations included food and horticultural crops for areas with low erosion and plantation crops for areas with very high erosion.